2020
DOI: 10.2478/acph-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effective and sensitive TLC-densitometric identification of meloxicam

Abstract: The influence of different chromatographic conditions and the process of spot visualization on determining the limit of detection as well as quantification (LOD and LOQ) of meloxicam by TLC-densitometric technique was estimated. Of all chromatographic conditions tested, the lowest limiting values, thus the best sensitivity, in the NP-TLC system was achieved on silica gel 60F254 and neutral aluminum oxide plates developed with the mobile phase consisting of ethyl acetate/toluene/n-butylamine (2:2:1, V/V/V). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…As shown in Table a, the recoveries and relative standard deviations (RSDs) are in the ranges of 96.85–104.64% and 0.84–5.21%, respectively. The detection limit (3σ/ k , σ is the standard deviation) of MLX is found to be 2.31 × 10 –2 nM, which is lower than most of those reported by the traditional analysis methods, , suggesting the high sensitivity of 1 to MLX. The luminescence change of 1 caused by the addition of MLX is fast, with a response time of about 5 s (Figure ).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…As shown in Table a, the recoveries and relative standard deviations (RSDs) are in the ranges of 96.85–104.64% and 0.84–5.21%, respectively. The detection limit (3σ/ k , σ is the standard deviation) of MLX is found to be 2.31 × 10 –2 nM, which is lower than most of those reported by the traditional analysis methods, , suggesting the high sensitivity of 1 to MLX. The luminescence change of 1 caused by the addition of MLX is fast, with a response time of about 5 s (Figure ).…”
Section: Resultsmentioning
confidence: 67%
“…Meloxicam (MLX), chemically named [4-hydroxy-2-methyl- N -(5-methyl-2-thiazolyl)-2H-1,2-benzothiazine-3-carboxamide-1,1-dioxide] (Scheme a), is a novel nonsteroidal anti-inflammatory drug (NSAID) with analgesic and antipyretic properties and has been widely applied to relieve symptoms of inflammation and pain. MLX is stable in water for more than 7 days at room temperature, but on the other hand, it has become one of the common microcontaminants in surface waters and sewage. , Some traditional analysis methods, such as high-performance liquid chromatography (HPLC), , thin-layer chromatography (TLC), spectrophotometric, and electrophoresis, have been developed for the determination of MLX. For example, Alina et al first reported the use of visualization agents to detect MLX on a thin layer recently . These methods have characteristics of high selectivity and good precision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation